2013
DOI: 10.4028/www.scientific.net/amm.311.196
|View full text |Cite
|
Sign up to set email alerts
|

Applying Frequency Bands to Explore the Identification of Two Dimensional Figures

Abstract: The aim of this study was to apply frequency bands to explore how mental rotation strategies affect the identification of 2D figures. Eighteen adults were recruited for this study. In the ERP experiments, the participants were required to identify 2D figures with mental rotation. The results showed the differences between the high-achieving (HA) and low-achieving (LA) spatial ability participants in their use of mental rotation for identifying 2D figures. At 300-380 ms, the HA participants showed higher brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Similarly, total and theta TRP were signi cantly higher in FA when CAD modelling from the orthographic projection. High F theta was previously reported by Liu et al 47 during mental rotations task and related to higher requirements on attention during the task 48 .…”
Section: Activation Of the Cortical Areas Across The Frequency Bandssupporting
confidence: 53%
See 2 more Smart Citations
“…Similarly, total and theta TRP were signi cantly higher in FA when CAD modelling from the orthographic projection. High F theta was previously reported by Liu et al 47 during mental rotations task and related to higher requirements on attention during the task 48 .…”
Section: Activation Of the Cortical Areas Across The Frequency Bandssupporting
confidence: 53%
“…For example, neuroimaging studies have shown that O cortical area is highly activated when perceiving the visual representations. Furthermore, previous studies have reported the highest TRP in the F and C areas during mental rotation task 47 . In line with these ndings, signi cant difference was noticed between the FA and RA when interpreting orthographic projection in the herein presented study.…”
Section: Activation Of the Cortical Areas Across The Frequency Bandsmentioning
confidence: 69%
See 1 more Smart Citation
“…Some findings may be extracted from the studies that captured engineers' EEG signals while solving design tasks; however, only a few of them segmented design tasks into epochs relatable to the visual processing of information (e.g. Nguyen et al 21 ).Previous EEG studies from other fields (primarily cognitive psychology) often investigated the visual processing of information through standardized tests (such as the mental rotation test) related to the aspects of visuospatial thinking (such as spatial visualization and mental rotation) [22][23][24][25][26][27] . The results of these previous studies imply that the higher power in the theta and beta frequency bands reflect the cognitive processing of visuospatial information [22][23][24][25] .…”
mentioning
confidence: 99%
“…The results of these previous studies imply that the higher power in the theta and beta frequency bands reflect the cognitive processing of visuospatial information [22][23][24][25] . For example, Liu et al 26 reported increased (compared to the baseline) theta and beta band power in the frontal cortical area when solving the mental rotation task. In addition, an increase in theta band power over the frontal cortical area has been related to attention allocation during the task 28 .…”
mentioning
confidence: 99%